2005
DOI: 10.1111/j.1600-0870.2005.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

A multi-model superensemble algorithm for seasonal climate prediction using DEMETER forecasts

Abstract: A B S T R A C TIn this paper, a multi-model ensemble approach with statistical correction for seasonal precipitation forecasts using a coupled DEMETER model data set is presented. Despite the continuous improvement of coupled models, they have serious systematic errors in terms of the mean, the annual cycle and the interannual variability; consequently, the predictive skill of extended forecasts remains quite low. One of the approaches to the improvement of seasonal prediction is the empirical weighted multi-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…In general, the MME prediction is superior to the predictions made by any single-model component for both two-tier systems (Krishnamurti et al 1999(Krishnamurti et al , 2000Palmer et al 2000;Shukla et al 2000;Barnston et al 2003) and one-tier systems Doblas-Reyes et al 2005;Yun et al 2005). A number of international projects have organized multi-model intercomparison and synthesis, among which the most comprehensive projects are the European Union-sponsored ''Development of a European Multi-model Ensemble System for Seasonal to InterAnnual Prediction (DEMETER; Palmer et al 2004) and the Climate Prediction and its Application to Society (CliPAS) project, sponsored by the Asian-Pacific Economic Cooperation (APEC) Climate Center (APCC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the MME prediction is superior to the predictions made by any single-model component for both two-tier systems (Krishnamurti et al 1999(Krishnamurti et al , 2000Palmer et al 2000;Shukla et al 2000;Barnston et al 2003) and one-tier systems Doblas-Reyes et al 2005;Yun et al 2005). A number of international projects have organized multi-model intercomparison and synthesis, among which the most comprehensive projects are the European Union-sponsored ''Development of a European Multi-model Ensemble System for Seasonal to InterAnnual Prediction (DEMETER; Palmer et al 2004) and the Climate Prediction and its Application to Society (CliPAS) project, sponsored by the Asian-Pacific Economic Cooperation (APEC) Climate Center (APCC).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the combination of the worst models may not always yield the lowest skill. Many studies have been carried out to find the optimal combination of MME to improve forecast skill (Krishnamurti et al 1999(Krishnamurti et al , 2000Kang et al 2002;Yun et al 2005;Yoo and Kang 2005;Doblas-Reyes et al 2005;Kug et al 2008). The highest MME skill may be achievable by an optimal choice of a subgroup of models, drawing upon an individual model's skill and the mutual independence among the chosen models (Yoo and Kang 2005).…”
Section: Effect Of the Number Of Models On Mme Predictionmentioning
confidence: 99%
“…Because the AIR obtained by spatial averaging of the ISMR can increase the correlation relative to the ISMR relation at the grid points (Saha et al, 2006), the forecast quality of AIR interannual variability has been assessed in this section, on the basis of the basic measurement of verification metrics (Yun et al, 2005): anomaly correlation coefficient (ACC) and root mean square error (RMSE).…”
Section: Seasonal Forecast Quality Of Air Interannual Variability In mentioning
confidence: 99%
“…Finally, techniques for constructing optimal MME forecasting have been developed (Krishnamurti et al, 2000;Doblas-Reyes et al, 2005). These approaches of the MME have shown some prospect in improving the seasonal forecast quality of precipitation beyond the individual models (Yun et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, the simple multi-model average does not take into account the quality differences between the models; therefore, it is expected that a weighted average, with weights based on the past performances of the models, will provide better predictions than the simple average. As expected, it was shown that the weighted average of climate models can improve predictions when using ensembles of AGCMs (Rajagopalan et al, 2002;Robertson et al, 2004;Yun et al, 2003), AOGCMs (Yun et al, 2005;Pavan and Doblas-Reyes, 2000;Chakraborty and Krishnamurti, 2009) and regional climate models (Feng et al,…”
Section: Introductionmentioning
confidence: 94%